Kondisi arus pasang surut di perairan pesisir kota Makassar , Sulawesi Selatan - Taslim Arifin; Yulius Y; Muhammad Furqon Azis Ismail (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2012)
Abstract. Numerical hydrodynamics model MOHID based on General Ocean Turbulence Model formula was used to study the tidal current in Makassar waters. The data used in this model are tidal elevation and bathymetry data from GEBCO. The tidal current simulation was conducted for 30 days. Model simulation results show that the tidal current velocity ranged between 0,001 m/s – 0,012 m/s. The current velocity during neap tide is smaller than the velocity during spring tide. The pattern of tidal current in Makassar waters is dominantly flows towards westward and then turned heading northward direction. The simulation result of tide-induced residual current in verification point shows that the flows is ebb-dominant at a rate of 0,005 m/s heading westward direction.